THE EFFECT OF SERVICE QUALITY AND PRICE ON PURCHASE DECISIONS MEDIATED BY BRAND IMAGE - Franco Pranoto; PM. Budi Haryono; Adrie Frans Assa (ID Solutions, 2022)
This study examines the effect of service quality and price on purchasing decisions mediated by brand image. The sample in this study were consumers of PT. Arista Auto Prima Honda in Aceh from Maybank Finance consumers. Based on the results of direct hypothesis testing, it is known that service quality affects brand image. Price affects brand image. Brand image affects purchasing decisions. Quality of service affects purchasing decisions, and prices affect purchasing decisions. Furthermore, brand image mediates definitively and significantly the relationship between service quality and purchasing decisions. Brand image partially and significantly mediates the relationship between price and purchasing decisions.